Penilaian Kinerja Rumah Sakit Metode Balanced Scorecard – Implementasinya Pada Dekade Ketiga : Scoping Review: - - Lasma Frisca Yoselina Panjaitan; Amal Chalik Sjaaf; Roza Falinda (LPPM Hang Tuah Pekanbaru, 2022)
Background : Balanced score card (BSC) has been for decades used as a performance measurement tool in many healthcare setting including hospital. Hospital performance measurement is essential to gauge, spesifically during the covid-19 pandemic where many hospitals are experiencing difficulties to sustain. Balanced Scorecard (BSC) is one of the widely used method to improve hospital performance for it’s comprehensiveness. The method applied four perspectives, those are financial perspective, growth and learning, custumor, and internal process. The aim of this study is to review the development of BSC implementation in hospitals across the globe in the 3rd decade, and the benefit to implement in local hospitals. Method : Research method is scoping review. The search manually started by studying related articles. Key words used to search articles are Hospital Performance and Balanced Scorecard, hospital performance measurement through data base EMBASE, MEDLINE and PuBMed. Result : 400 records were identified and 23 underwent a full text review. 10 articles were included. BSC in hospital setting has developed, not only as a performance evaluation tool but also to drive performance by integrating BSC as mapping strategy. This study shows that most hospitals still adapt the 2nd generation of BSC, mapping strategy. Only one hospital performed the destination statement. A few of which applies it as a tool to measure performance Conclusion : BSC has been implemented as performance management tool in hospitals worldwide. There have been improvements in the 3rd decade, its not only for monitoring performance as mapping strategy to approach hospital’s goals..